‘But the Dutch would call it exploitation’: crimmigration and the moral economy of the Chinese catering industry in the Netherlands - Hiah, Jing (Crime, law and social change, 2016)
Based on qualitative research into the Chinese catering industry in the Netherlands, this article describes labour relations between Chinese employers and their (undocumented) employees against the background of a society in which criminal, administrative, and immigration law increasingly converge. The authors argue that the intertwining of these three fields of law asks for an adaptation of the concept of crimmigration. Furthermore the authors claim that an overemphasis on the legal definition of ‘labour exploitation’ distances law from the people it addresses as it reduces employers to offenders and employees to victims. Such a normative perspective prevents us from gaining further insights into underlying issues such as illegal stay, informal labour practices and labour relations within migrant niches. The authors argue on the contrary that Chinese restaurant owners and their employees operate in a ‘moral economy’ where labour relations are influenced not only by formal rules and a demand for reasonably priced food and flexible, motivated, inexpensive and skilled employees, but also by informal rules and culturally shared expectations about justice and reciprocity.